Long-Term Agricultural Management Alters Soil Fungal Communities and Soil Carbon and Nitrogen Contents in Tea Plantations - Ying Luo; Shaobo Zhang; Qiang Hu; Fuyin Huang; Demeng Bao; Xin Li; Chunwang Dong; Shuixing Zhu; Jianyu Fu; Peng Yan (Agronomy)
Soil carbon (C) and nitrogen (N) are vital for enhancing tea production and ensuring the sustainability of tea plantation ecosystems. However, research on the dynamics of soil C and N pools and their associated microbial mechanisms in tea plantations with varying cultivation durations is scarce. We compared soil samples from a forest and two tea plantations—young established (YTP) and century-old (OTP)—to assess changes in soil C and N concentrations and the impact of fungal community structure on these elements. Soil organic carbon (SOC) and total nitrogen (TN) were markedly higher in OTP than in the YTP and forest (65.9% and 30.1%, respectively, relative to YTP). Eurotiomycetes in the YTP group accounted for a relatively higher proportion at 51.6%, surpassing its presence in both the forest (14.3%) and OTP (4.78%) groups and it can be the main microbial factor affecting the C cycle in tea plantation soils and facilitating SOC mineralization. Enhancing planting years or changing land use patterns improves fertilizer and biomass sedimentation and increases the relative abundance of Eurotiomycetes in the soil and the C sink potential of tea plantations. This study provides valuable insights into the role of soil C and N dynamics and fungal communities in tea plantation ecosystems, highlighting the importance of managing these factors for sustainable tea production.